Saints in politics the "Clapham Sect" and the growth of freedom - Howse, Ernest Marshall (London, UK Allen and Unwin, 1953)
Includes bibliographical references and index.
Keywords: Clapham Sect; Great Britain -- social reform -- Clapham Sect -- 1783-1833.; Christianity and politics